Physical activity during pregnancy - literature review - Mazur, Karol; Machaj, Dominik; Mazur, Dominika (Journal of Education, Health and Sport, 2020)
Physical activity is one of the basics elements of a healthy lifestyle. Pregnancy is a unique state of physiologic stress which necessitates physical, mental, and social adaptation. Physical activity has significant influence on health of pregnant women. the most important benefits of physical exercising during pregnancy are: preparation for labor effort and reduction of the duration of the labor. The form of the physical activity should be consulted with the midwife or ginecologist, that will choose adequate exercises to the need and possibilites of the pregnant woman. The aim of this study was to evaluate meaning of the physical activity during pregnancy for the women. The status of women’s knowledge about physical exercises in pregnancy is unsatisfactory. The internet isthe main source of information about physical activity during pregnancy for pregnant women. There is significant correlation between the awerness of meaning of physical activity during pregnancy and the age, education, attending on childbirth education classes or education of pregnant women. The level of knowledge about meaning of physical activity during pregnancy, time of beginning the exercising, their frequency and the type, contraindications is high in the group of women over 30 years old, married, with high level of education, multiparas and those who attended childbirth education classes. Physical activity during pregnancy is often determined by gestational age, course of pregnancy and exercising before pregnancy. Unfourtanely many women stop physical exercising during pregnancy, especially in the first trymester. Main reasons to stop physical exercising are: general feeling of being unwell, medical recommendations, and symptomps related to pregnancy. The most adequate sports for pregnant women are: swimming, yoga, pilates and gymnastics, that are often organised in childbirth education classes Also many pregnant women don’t consultate physical exercising during pregnancy with the gynecologist or midwife.